TermFinder: creating online termbanks of technical terms for early university study. Issue 2 (25th August 2015) - Peters, Pam; Jones, Alan; Smith, Adam; Winchester-Seeto, Theresa; Middledorp, Jenny; Petocz, Peter
Abstract : The TermFinder project is a new kind of collaboration between academic specialists/teachers and applied linguists/terminographers in creating specialized online termbanks for pedagogical purposes. Although there are technical glossaries on the internet, their ad hoc definitions do not target the needs of novices in the discipline, or those with limited English. Specialized terminology remains a substantial barrier for tertiary students grappling with the foundation concepts, overshadowed by the recent emphasis on generic skills. TermFinder termbanks are customized for designated courses, and informed by a computerized corpus of lecture materials and reading texts used by the lecturer. The terminographer uses the corpus to identify the key terms by frequency and to source natural examples of their usage: their grammar as well as their technical sense(s) and connections with other terms in the discipline. The methodology is new for terminography (ie the description of terminology), though well established in general lexicography. This corpus-informed terminography is also pedagogically-informed, in that the selection and definitions of terms are reviewed in consultation with disciplinary teaching staff. It ensures that (a) necessary lower frequency terms are included; and (b) the definitions drafted by the terminographer are conceptually adequate for the level of student. Pilot testing of the statistics termbank confirms its pedagogical value. TermFinder pages contain verbal, audio and graphic elements to develop students' understanding of disciplinary concepts through multiple cognitive channels.